Peranan Etika Profesi Pendidik dalam Pembentukan Karakter Peserta Didik - Isnawardatul Bararah (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Character education does not only teach what is good and what is wrong to students, but character education also applies positive habituation, so that students are able to understand and carry out these values in saying and acting everyday. Educational governance in the context of ethical management must use the basis of general norms and morality that apply in society. Educational evaluation is not only determined by the success of academic achievement alone, but that success is measured by the paradigm of morality and social and religious values. This benchmark must be an integral part in assessing the success of an educational activity. By using a literature study, this study shows that the ethics of the teaching profession is an application of general ethics that governs teacher behavior. The norms of morality are the basis on which the profession refers in its behavior. The basis for their behavior is not only educational laws and educational procedures that encourage teacher behavior, but values, morals, and ethics are also important references that must be used as the basis for policy.